Effects of Moderate Aerobic Exercise Training on Vascular Health and Blood Pressure in African Americans - Feairheller, Deborah L. (John Wiley and Sons Inc., 2014)
As healthcare progresses toward individualized medicine, understanding how different racial groups respond to lifestyle interventions is valuable. It is established that African Americans have disproportionate levels of cardiovascular disease and impaired vascular health, and clinical practice guidelines suggest lifestyle interventions as the first line of treatment. Recently, the authors reported that 6 months of aerobic exercise improved inflammatory markers, flow‐mediated dilation (FMD), and levels of circulating endothelial microparticles (EMPs) in African American adults. This study is a subgroup analysis of the aerobic exercise–induced changes in vascular health and blood pressure (BP) measures, including carotid artery intima‐media thickness (IMT), nitroglycerin‐mediated dilation (NMD), ambulatory BP, and office BP. Sedentary African American adults (53.4±6.2 years; 21 women and 5 men) showed improved vascular health but no change in BP. Carotid artery IMT decreased 6.4%, plasma nitric oxide levels increased 76.6%, plasma EMP levels decreased, percentage of FMD increased 59.6%, and FMD/NMD ratio increased 36.2% (P<.05 for all). Six months of aerobic exercise training is sufficient to elicit improvements in vascular structure and function in African Americans, even without improvements in BP measures or NMD (ie, smooth muscle function). To our knowledge, this is the first study to report such findings in African Americans.